Maqāṣidī Interpretation of Qur’anic Social Verses: Reconstructing Social Justice in Contemporary Contexts: Penafsiran Maqāṣidī terhadap Ayat-ayat Sosial dalam Al-Qur'an: Merekonstruksi Keadilan Sosial dalam Konteks Kontemporer - Akmal Gunawan; Abdul Aziz Harahap; Syahrul Gunawan (Takwil: Journal of Quran and Hadith Studies, 2026)
This study aims to analyze social verses in the Qur’an through the maqāṣidī interpretation approach and to examine their relevance in promoting social justice in contemporary society. The research focuses on how the concept of social justice is constructed in the Qur’an and how maqāṣid al-sharī‘ah can be used as an analytical framework to contextualize these values. This study employs a qualitative method using library research, with data collected from primary sources such as the Qur’an and classical as well as contemporary tafsir literature, supported by recent academic journal articles. The findings reveal that Qur’anic social justice is structured in three main dimensions: normative justice as a universal principle, relational justice based on human equality, and structural justice reflected in governance and legal systems. Through the maqāṣidī approach, these dimensions are interpreted as part of the broader objective of achieving public welfare (maṣlaḥah) and protecting human dignity. The impact of this research highlights that maqāṣidī exegesis provides a contextual and applicable framework for addressing modern social issues such as inequality, discrimination, and injustice. It also contributes theoretically by proposing the concept of maqāṣid-based social justice as a dynamic and integrative paradigm in contemporary Qur’anic studies.